Low SAR Multi-Coupling Feed Antenna and Multi-Device MIMO System Design: Suitable for Multi-Band Wireless Communications - Ming-An Chung; Zhi-Xuan Zhang; Chia-Chun Hsu; Chia-Wei Lin (IEEE Access)
This article introduces the design of a multi-coupling feed antenna (MCFA) appropriate for 4G LTE, 5G NR (sub-6 GHz), and WLAN frequency bands. Most antenna designs used in different consumer electronic products only include specific 5G NR frequency bands, while the MCFA antenna proposed in this article covers applications in multiple frequency bands and will meet the needs of more communication devices. MCFA is designed on an FR-4 substrate and uses the coupled-feed structure to achieve diverse operating frequencies. This article also uses the antenna to construct a multi-coupling feed antenna MIMO system (MCFA-MIMO system), which is suitable for electronic devices such as laptops, smartphones, and Wi-Fi base stations. The antenna uses a simple structural design and does not require any RLC components to achieve multiple operating frequency bands, isolation below -11dB, a maximum gain of 4.7, and a maximum efficiency of 78%. The measurement and simulation results of the proposed antennas prove that each multi-band antenna performs consistently in MIMO systems and has high gain and high isolation performance. The simulation values of the specific absorption rate (SAR) of MCFA-MIMO system comply with international specifications and will not harm human health. This makes this antenna design a candidate for modern portable electronic devices.